2019
DOI: 10.12944/cwe.14.2.18
|View full text |Cite
|
Sign up to set email alerts
|

Work - Related Musculoskeletal Disorders: A Case Study of Sawmill Workers in Bangladesh

Abstract: Sawmill workers in Bangladesh are increasingly at risk of emerging work-related musculoskeletal disorders (WRMSDs). Their jobs involve awkward manual handling tasks such as lifting, carrying, pushing and pulling. These are identified as risk factors for musculoskeletal disorders. The aims of this study are to find out the prevalence of musculoskeletal disorders and assessing the postural risk level among sawmills workers. This cross-sectional study was conducted with 254 workers from 60 sawmills at the souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 12 publications
(2 reference statements)
2
7
1
Order By: Relevance
“…This finding is in line with the findings of other studies on MSDs in Saudi Arabia (Alghadir and Anwer, 2015) and China (Yan et al, 2017). Work experience was also positively associated with MSDs, which is similar with other studies (Ekpenyong and Inyang, 2014) and (Rahman et al, 2019). Moreover, multiple logistic regression modelling showed that three key factors remained significantly associated with MSDs among quarry workers.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This finding is in line with the findings of other studies on MSDs in Saudi Arabia (Alghadir and Anwer, 2015) and China (Yan et al, 2017). Work experience was also positively associated with MSDs, which is similar with other studies (Ekpenyong and Inyang, 2014) and (Rahman et al, 2019). Moreover, multiple logistic regression modelling showed that three key factors remained significantly associated with MSDs among quarry workers.…”
Section: Discussionsupporting
confidence: 91%
“…Workers who are not obese have 0.17 less odd of developing this disorder. Similar finding was indicated in a study among sawmill workers in Bangladesh, whereby their BMI was significantly associated with MSDs (Rahman et al, 2019).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…stated the mean working time as 11 hours. [ 14 ] This is in contrast to our study where we found effective working hours as 8 hours. In the study by Sutcu A and Semerci NT, they found female employees as 3.6% only and more than half of the employees were from 30 to 40 years and three fourth employees had primary education.…”
Section: Discussioncontrasting
confidence: 99%
“…Musculoskeletal disorders (MSDs) usually occur due to heavy physical work, static working postures for a long duration, frequent bending, squatting, and twisting postures, manual material handling, and repetitiveness of work [5]. In the sawmill industry, workers repetitively perform massive manual tasks for a prolonged duration, which could lead to severe physical stress among them [6]. According to Das [7,8], brickfield workers suffer from musculoskeletal pain due to working for a long period of time without meeting ergonomic requirements.…”
Section: Introductionmentioning
confidence: 99%